HUBUNGAN WAKTU TUNGGU MENUJU OPERASI PENGANGKATAN TUMOR INTRAKRANIAL DENGAN SKALA PERFORMA KARNOFSKY PASCAOPERASI - Setyo Widi Nugroho; Aryandhito Widhi Nugroho; Renindra Ananda Aman; Hanif Gordang Tobing (NEURONA, 2020)
Introduction: The waiting time to elective intracranial tumor removal surgery in Indonesia is unknown, let alone its association with postoperative functional outcome. Aim: To identify the waiting time to elective intracranial tumor removal and to analyze its association with poor functional outcome, defined by 3-months postoperative Karnofsky Performance Scale (KPS score) of <70. Methods: This medical record-based retrospective study was performed on intracranial tumor patients underwent elective tumor removal surgery in 2016. Multivariable logistic regression analyses were utilized to determine any significant association between waiting time to elective intracranial tumor removal surgery and poor functional outcome, adjusting for age, sex, preoperative KPS score, pre- and postoperative tumor volume, percentage of tumor removal, tumor histopathology, and grading. Results: Data were obtained from 191 patients, with histopathology distributions as follows: 49% meningiomas, 22% pituitary adenomas, 9% astrocytomas, 3% metastatic tumors, 3% primary central nervous system lymphomas, 2% oligodendrogliomas, 2% craniopharyngiomas, and 10% others. Overall median (min-max) of waiting time to elective intracranial tumor removal surgery was 35 (0-529) days. Significant association between waiting time to elective intracranial tumor removal surgery and poor functional outcome was evident in univariable analysis (OR 1.004), but not in multivariable analysis. The collinearity value of pre- and postoperative tumor volume, percentage of tumor removal with waiting time were, respectively, 5.92; 5.69; and 3.2. Discussion: There was no significant association between waiting time to elective intracranial tumor removal surgery and poor functional outcome. Strong collinearities were identified between pre- and post-operative tumor volume, percentage of tumor removal and waiting time to elective intracranial tumor removal surgery. Keywords: functional outcome, intracranial tumor, removal surgery, waiting time